Evaluation of using human growth hormone in post extraction dental socket preservation Clinical and radiologic study (Latakia University Journal -Medical Sciences Series, 2022)
The aim of this study is to evaluate the effectiveness of the use of growth hormone (somatropin) in preserving the dimensions of alveolar bone after dental extractionTechniques for preserving the dimensions of the alveolar bone after tooth extraction are becoming a part of the usual clinical practice of oral and maxillofacial surgeons with the aim of minimizing post-extraction bony resorption and subsequent follow-up with implant insertion.The study sample consisted of 10 patients who were indicated for bilateral symmetrical tooth extraction, where the segmented mouth technique was followedThe material was applied to the tooth socket after its extraction by gelfoam and the radiographic follow-up was performed using CBCT scan to assess changes in the dimensions of the alveolar bone in the extraction area before and three months after the surgical procedure.The results showed a better preservation of the bony dimensions of the alveolar edge in the area of ​​application of the material in each patient, with a preference for better bone density in the socket where somatropin was applied .